PROMOÇÃO DA INTIMIDADE E SEXUALIDADE CONJUGAL E REPRODUÇÃO HUMANA ASSISTIDA - Haslinger, Camile (2022)
Infertility has been growing worldwide, reaching an estimated 20% of the world's population with difficulties to get pregnant. Data from the World Health Organization suggest that in Brazil, there are about 32 million couples of childbearing age, of which 6.5 million have problems related to infertility. Couples who receive a diagnosis of infertility may have their sexuality and intimacy affected, since this is an indication that goes against the expectations projected in the desire for the child and also in the couple's relationship. Studies in this area are in line with the objective of ensuring universal access to sexual and reproductive health services, including family planning, information and education, as well as the integration of reproductive health into national strategies and programs, mentioned in the 2030 Agenda of the Organization of United Nations. Objectives: To develop and implement, through a pilot study, a program to promote intimacy and sexuality for couples undergoing Assisted Human Reproduction treatment. Methodological Path: Study of a qualitative nature, developed from the 5W2H matrix, which comprises decision-making on the main elements that guide the implementation and execution of the program. The tool is composed of seven fields in which the following information must be included: What (What) must be done? Why (Why) should it be implemented? Who is responsible for the action? Where should it run? When (When) should it be implemented? How (How) should it be conducted? How much (How much) will the implementation cost? The 5W2H matrix guided the process of identifying the challenge faced by the target population, through a literature review; guided the definition regarding the structure of the program and its script; favored the design of the program in the online format, with a view to expanding its reach, and revealed its costs. Having developed the program for the promotion of intimacy and sexuality for couples undergoing Assisted Human Reproduction treatment, a pilot study was carried out based on a single case. One of the Brazilian couple participated, heterosexual, in Assisted Human Reproduction treatment for three years. The participating couple answered a questionnaire and an interview that sought to assess their perception of their intimacy and sexuality. Subsequently, the couple participated in the proposed program and received the e-book. Finally, the e-book was evaluated by an editorial committee composed of four “experts” in the area. The Results: 1st. With regard to the development and implementation of the “Entrelaços” program, the importance of the product is noted for the maintenance of mutual interest and closeness of couples who are undergoing Assisted Human Reproduction treatment, in terms of promotion, intimacy and sexuality, as well as for professionals who allocate the your look at this population. 2nd Through the responses of the participating couple, regarding their intimacy and sexuality during the Assisted Human Reproduction treatment, it was possible to identify that even in treatment, they try to maintain quality intimate moments, but consider that the frequency of intimate encounters could be greater. 3rd. The results of the editorial commission's evaluation guided the improvement of the e-book, which started with contributions regarding writing and spelling revision. The committee generally considered the material to be suitable for the intended audience. Final Considerations Product generated and applicability: The program developed and implemented through a pilot study, was entitled 'Entrelaços' and included eight videos on intimacy and sexuality and the reflexes on conjugality and an e-book, for the promotion of intimacy and sexuality of couples in the process of assisted human reproduction. The applicability of the program is due to the need to address issues involving intimacy and marital sexuality in Assisted Human Reproduction treatment, as well as helping health professionals who wish to develop and implement a program that aims to promote health and populations' quality of life.